Perubahan Afiliasi Politik Ulama Pesantren NU Masa Transisi Demokrasi di Wilayah Eks-Keresidenan Surakarta (1998-2004) - Alam, M. Bagus Sekar (Jurnal Review Politik, 2018)
This Article describes about the dynamic changes of NU Pesantren Ulama Political Affiliation transformation in ex-Keresidenan Surakarta Region during Democratic transition period (1998-2004). Historical approach was selected as a tool to get the comprehensive narrative explanation. During 1998 reformation, Indonesia experienced the euforia of democrative wave of changing to become more free in political stage. NU pesantren ulama became more free returning in politic. The first political movement by NU pesantren ulama during this era was established and raised Partai Kebangkitan Bangsa (PKB) just before 1999 national election. Their purpose by establishing new party was to put their representatives in government (legislative and executive). The fact that happened after NU pesantren ulama returned in politic was not good. These NU pesantren ulama had forgotten their main role and tasks in socio-religious and moslem community. Because of that fact in the beginning of 2004 election the majority of NU pesantren ulama in this region returned to their professionalism which standing neutral above their political interest.